Efficiency of Government Expednitures and Their Effects on Inter-regional Convergence: A Case Study of Indonesia - Hans, Michael; Prasetyia, Ferry (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The implementation of national development cannot be separated from the role of the government through the programs it funds. Government spending is generally allocated to productive activities that can basically contribute to reducing disparities between provinces in Indonesia. However, not all of this government spending ends in waste alone. Based on this, this study aims to measure the extent to which publik spending efficiency can contribute to the convergence of economic growth in Indonesia by using government function spending data from 34 provinces for the period 2017 to 2022 taken from the Ministry of Finance of the Republic of Indonesia. Furthermore, dynamic panel data estimation uses the Generalized Method of Moment (GMM) method to obtain the economic growth convergence coefficient.